Differentiation of Approaches to Determination and Measurement of Poverty in Modern Latvia and Ways to Improve Social Policy - Tsaurkubule, Zhanna (Social Welfare: Interdisciplinary Approach, 2021)
The article analyzes the population’s poverty problem, importance of which has increased significantly in Latvia. The basic concepts and approaches to measuring poverty, macroeconomic conditions and social policy instruments used to prevent and reduce poverty are considered. By investigating the interrelation of different characteristics of poverty, a polynomial forecast of the poverty dynamics of the Latvia’s population is made. For the development of specific measures to reduce the poverty of population, factors causing current situation were identified.